2022
DOI: 10.1007/s42235-022-00314-w
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Materials: From Distinct Dimensional Architecture to Thermal Regulation Properties

Abstract: The structural evolutions of the organisms during the development of billions of years endow them with remarkable thermal-regulation properties, which have significance to their survival against the outer versatile environment. Inspired by the nature, there have been extensive researches to develop thermoregulating materials by mimicking and utilizing the advantages from the natural organisms. In this review, the latest advances in thermal regulation of bioinspired microstructures are summarized, classifying t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 149 publications
0
2
0
Order By: Relevance
“…The physical phase composition and lattice structure of PLMs can vary due to differences in their preparation processes. Notably, these structural variations often lead to changes in the physicochemical properties of the materials, which in turn can affect their interactions with plants [21][22][23][24][25]. As observed in Figure 1, the diffraction peak intensities of rPLM and bPLM align closely with the corresponding peak positions in the PDF standard cards 01-075-0265 (Sr .75 Ca .25 S) and 00-015-0016 (Sr 2 MgSi 2 O 7 ), respectively.…”
Section: Analysis Of Physical Phase Statesmentioning
confidence: 62%
“…The physical phase composition and lattice structure of PLMs can vary due to differences in their preparation processes. Notably, these structural variations often lead to changes in the physicochemical properties of the materials, which in turn can affect their interactions with plants [21][22][23][24][25]. As observed in Figure 1, the diffraction peak intensities of rPLM and bPLM align closely with the corresponding peak positions in the PDF standard cards 01-075-0265 (Sr .75 Ca .25 S) and 00-015-0016 (Sr 2 MgSi 2 O 7 ), respectively.…”
Section: Analysis Of Physical Phase Statesmentioning
confidence: 62%
“…This finding aligns with previous studies that have identified certain limitations of proteinoids as bioinspired materials. These limitations include low stability, reproducibility, and scalability [ 23 , 24 ]. Hence, we propose that proteinoids should undergo additional optimisation and modification in order to improve their acoustic capabilities and potentially surpass the capabilities of the current device.…”
Section: Discussionmentioning
confidence: 99%
“…This finding aligns with previous studies that have identified certain limitations of proteinoids as bioinspired materials. These limitations include low stability, reproducibility, and scalability [20,21]. Hence, we propose that proteinoids should undergo additional optimisation and modification in order to improve their acoustic capabilities and potentially surpass the capabilities of the current device.…”
Section: Discussionmentioning
confidence: 99%